Perubahan Harga Dalam Transaksi Jual Beli Bawang Merah Perspektif Fiqih Jual Beli - zainudin, muhammad (Jurnal Ilmiah Ekonomi Islam, 2023)
In Islam, buying and selling is an important aspect of the economic life of Muslims. The principles of buying and selling fiqh governing these transactions, such as honesty, fairness and agreement, serve as guidelines for Muslims in transactions. The aim of the research is to change the transaction price of shallots made by the ordering/buying party, which is viewed from the perspective of buying and selling jurisprudence. The research method used by researchers in this study is qualitative. This approach uses a descriptive analytical method, namely a method that functions to describe or give an overview of the object under study through data or samples and make conclusions that apply to the public. The results of this study indicate that the price changes made by the ordering/buyers menzholimi shallot traders or sellers by violating the fiqh of buying and selling and Islamic Shari'a. As mentioned in surah An-Nisa verse 29.